2021
DOI: 10.1097/md.0000000000026841
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of delayed sputum smear conversion among pulmonary tuberculosis patients in Kota Kinabalu, Malaysia

Abstract: Smear-positive pulmonary tuberculosis (SPPTB) is the major contributor to the spread of tuberculosis (TB) infection, and it creates high morbidity and mortality worldwide. The objective of this study was to determine the predictors of delayed sputum smear conversion at the end of the intensive phase of TB treatment in Kota Kinabalu, Malaysia.This retrospective study was conducted utilising data of SPPTB patients treated in 5 TB treatment centres located in Kota Kinabalu, Malaysia from 2013 to 2018. Pulmonary T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 30 publications
4
9
0
Order By: Relevance
“…Table 4 outlines the comparison of our prevalence data with a few recent studies in the past five years. Our finding is consistent with another Malaysian study which was also conducted in Sabah in different research sites, where they identified 7.2% of patients having delayed sputum conversion from 2013 to 2018 [ 14 ]. In comparison, our prevalence of delayed sputum conversion was not too high.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Table 4 outlines the comparison of our prevalence data with a few recent studies in the past five years. Our finding is consistent with another Malaysian study which was also conducted in Sabah in different research sites, where they identified 7.2% of patients having delayed sputum conversion from 2013 to 2018 [ 14 ]. In comparison, our prevalence of delayed sputum conversion was not too high.…”
Section: Discussionsupporting
confidence: 92%
“…Ibrahim (2022) and Bhatti (2021) reported a higher prevalence of 19.1% and 30.5% respectively in Malaysia [ 15 , 16 ]. Similar large variation of prevalence data was observed globally as observed in Table 4 (8.3% to 35%), and as reported in earlier studies, from 8% in Cameroon up to 30% in Cleveland [ 14 21 ]. This variation is observed despite the relatively standardized, effective first-line regime for antituberculous therapy worldwide.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…8,9 The percentage of smear-positive patients with delayed sputum smear conversion at the end of the intensive phase of anti-TB treatment is an indicator of the performance of the TB programme. 10 Thus, it is necessary to study the sputum non-conversion rates in different settings. In addition, a detailed study is necessary to be carried out to stratify the role of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Sputum non-conversion rates have been increasingly observed during the management of TB patients. 10 No significant study has been performed in recent years in Nepal to find out the prevalence of sputum JNMA I VOL 59 I ISSUE 243 I November 2021 non-conversion in patients undergoing anti-tubercular therapy and to stratify the role of various causes that might have contributed to the development of nonconversion.…”
Section: Introductionmentioning
confidence: 99%